Detrital zircon U–Pb geochronology constrains the age of Brazilian Neogene deposits from Western Amazonia - Bissaro-Júnior, Marcos C. (2019)
The fossiliferous beds of the Solimões Formation, western Brazilian Amazon have yielded several vertebrate fossils that are key to understand the evolution of Neotropical biotas. Although this sedimentary unit has been studied for more than two centuries, no absolute dates are available so far, preventing more precise bio/chronostratigraphic interpretations and broader comprehension of the biotic/geological events that affected this northern portion of South America during the Neogene. Here, we present the first Neogene radioisotopic dates for the Brazilian Amazon, via U-Pb dating of detrital zircon from two classical sites. Both samples have small proportions of relatively young zircon grains, the dates from which are the maximum ages of deposition. LA-ICPMS analysis of two grains from the Niterói locality yielded a weighted mean of 8.5 ± 0.5 Ma and CA-TIMS analysis of two grains from the Talismã locality yielded a weighted mean of 10.89 ± 0.13 Ma. These maximum deposition ages are in the Tortonian stage, late Miocene, confirming the age previously inferred based on biochronological data.